2017
DOI: 10.1113/jp273123
|View full text |Cite
|
Sign up to set email alerts
|

PITX2‐dependent gene regulation in atrial fibrillation and rhythm control

Abstract: Atrial fibrillation (AF) is a common arrhythmia. Better prevention and treatment of AF are needed to reduce AF‐associated morbidity and mortality. There are several major mechanisms that cause AF in patients, including a genetic predisposition to develop AF. Genome‐wide association studies have identified genetic variants associated with AF populations, with the strongest hits clustering on chromosome 4q25, close to the gene for the homeobox transcription factor PITX2. The effect of these common gene variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
42
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 59 publications
0
42
0
3
Order By: Relevance
“…Pitx2 encodes a paired related homeodomain transcription factor that is essential for both human and mouse development. Investigations aimed at dissecting the biological role of Pitx2 are important, especially given that Pitx2 has been implicated in several human diseases, including Rieger syndrome, ocular dysgenesis with glaucoma, acute appendicitis and atrial fibrillation (AF), the most common sustained human arrhythmia (Ellinor et al, 2010;Gudbjartsson et al, 2007;Lin et al, 1999;Lu et al, 1999;Semina et al, 1996;Syeda et al, 2017). In postnatal cardiomyocytes (CMs), Pitx2 regulates genes that are important for the cellular response to reactive oxygen species (ROS), and is itself a target of Nrf2 (also known as Nfe2l2), a master transcriptional regulator of the cellular antioxidant response (Tao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Pitx2 encodes a paired related homeodomain transcription factor that is essential for both human and mouse development. Investigations aimed at dissecting the biological role of Pitx2 are important, especially given that Pitx2 has been implicated in several human diseases, including Rieger syndrome, ocular dysgenesis with glaucoma, acute appendicitis and atrial fibrillation (AF), the most common sustained human arrhythmia (Ellinor et al, 2010;Gudbjartsson et al, 2007;Lin et al, 1999;Lu et al, 1999;Semina et al, 1996;Syeda et al, 2017). In postnatal cardiomyocytes (CMs), Pitx2 regulates genes that are important for the cellular response to reactive oxygen species (ROS), and is itself a target of Nrf2 (also known as Nfe2l2), a master transcriptional regulator of the cellular antioxidant response (Tao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This locus is near the paired‐like homeodomain transcription factors ( PITX2 ) gene, which is critical for left‐right asymmetry of the pulmonary vein (PV) . Recent studies have shown that changes in PITX2c RNA levels can lead to a change in atrial membrane potential . Anatomically, the PV are an important source of triggers for the initiation of AF and a main target of catheter‐based treatment .…”
Section: Introductionmentioning
confidence: 99%
“…2 Recent studies have shown that changes in PITX2c RNA levels can lead to a change in atrial membrane potential. 3,4 Anatomically, the PV are an important source of triggers for the initiation of AF and a main target of catheter-based treatment. 5 However, there are no data regarding 4q25 variants and how they impact left atrial substrate.…”
mentioning
confidence: 99%
“…Fabritz and coworkers tackle the controversies surrounding the PITX2 gene in atrial fibrillation (Syeda et al . ). Based on genome‐wide association studies, the PITX2 gene locus is near many single nucleotide polymorphisms linked to high atrial fibrillation risk, but its mechanistic role in atrial fibrillation remains enigmatic.…”
mentioning
confidence: 97%